Performance of the silica adsorbent from snake fruit peel for removing heavy metals of Ag, Cu, Mn, and Cr in SCW - Salamah, Siti; Satar, Ibdal (Institute of Advanced Engineering and Science, 2024)
Silver crafts wastewater (SCW) typically contains environmentally harmful heavy metals, including Ag, Cu, Mn, and Cr, necessitating treatment before disposal. This study explores a promising solution using silica (SiO2) adsorbents derived from snake fruit peel through acidic activation with HCl concentrations of 2, 4, and 6 M. Qualitative analysis of the adsorbent involved Fourier-transform infrared spectrometer (FTIR) and x-ray fluorescence (XRF) techniques. XRF analysis revealed major compositions of Si (26%) and Cl (71.46%), with minor elements such as Ca (0.91%), P (0.42%), K (0.37%), Fe (0.12%), and others. FTIR analysis indicated the presence of siloxane (Si-O-Si) and silanol (Si-OH) on the adsorbent. The SiO2 adsorbent demonstrated effectiveness in removing heavy metals (Ag, Cu, Mn, and Cr) from SCW, achieving removal percentages of approximately 16.96%, 24.38%, 19.34%, and 9.82%, respectively. This research contributes to the development of an environmentally friendly approach for SCW treatment using silica adsorbents derived from agricultural waste.